Estudo de ciclos limites em uma classe de equações diferenciais descontínuas - Carvalho, Yagor Romano [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Neste trabalho temos como principal objetivo determinar quota inferior para o número máximo de ciclos limites de um sistema diferencial polinomial de Liénard descontínuo de grau n com m zonas, para m=2,4. A principal ferramenta é uma combinação da Teoria da Média de primeira ordem com o processo de regularização de sistemas descontínuos. Analisamos detalhadamente um caso particular de um sistema polinomial de Liénard de grau 3 com 4 zonas

In this work our main aim is to determine the lower upper bound for the maximum number of limit cycles of a m-piecewise discontinuous Liénard polynomial differential system of degree n, for m=2,4. The main tool is a combination of the first order Averaging Method with the regularization process of discontinuous systems. We analyzed in details a particular case of a 4-piecewise discontinuous Liénard polynomial differential system of degree 3.
Study of limit cycles in a class of discontinuous differential equations
Keywords: Ciclos limites; Método da média; Sistemas dinâmicos; Regularização; Limit cycles; Averaging method; Dynamical systems; Regularization